The prevalence of HPV infections in HPV-vaccinated women from the general population - Hamsikova, Eva; Smahelova, Jana; Ludvikova, Viera; Salakova, Martina; Rychla, Jana; Skrenkova, Jana; Rob, Lukas; Tachezy, Ruth (APMIS, 2017)
Currently, three prophylactic HPV vaccines are commercially available to prevent HPV 16/18 infection and associated lesions. The aim of the study was to assess markers of HPV infection in women/girls before vaccination and to ascertain the prevalence and spectrum of post-vaccination HPV types. Three hundred and thirty subjects of which 75 were virgins were enrolled. Before the first dose of the HPV vaccine and 1, 3 and 5 years after the completion of HPV vaccination, the samples for cytology, HPV detection and anti-HPV antibody response were taken. At enrolment, HPV DNA was detected in 38% of sexually active girls/women. At the first, second and third follow-up, HPV DNA was found in 40, 45, and 39% of them. The seroprevalence rates to HPV 6, 11, 16 and 18 in these subjects were 31, 21, 18 and 10%. On the follow-up significantly higher levels of antibodies to HPV 16/18 were found after application of divalent vaccine. Results of the study demonstrate high prevalence of HPV infection in young women. In a substantial number of women, HPV-specific antibodies as well as high-risk HPV types were detected. HPV-specific antibodies were also frequently found in non-sexually active girls. The acquisition of HPV after the onset of sexual life was very fast.
Keywords: infection; vakcíny proti papilomavirům; Papillomaviridae; DNA; mladiství; Cohort Studies; Middle Aged; cervix uteri; DNA virů; Papillomavirus Infections; Antibodies, Viral; Adult; mladý dospělý; kohortové studie; antibodies; infekce papilomavirem; Young Adult; ženské pohlaví; Humans; Seroepidemiologic Studies; persistence; DNA, Viral; lidé středního věku; protilátky virové; séroepidemiologické studie; HPV; dospělí; Papillomavirus Vaccines; Female; Adolescent; Cervix Uteri; lidé; vaccination